Conventional radiotherapy planning of cervical cancer in resource-constrained set-up: Utilizing soldering lead wire to delineate radiotherapy portal - Ramaiah Vinay Kumar (Elsevier, 2020)
Simulator for radiotherapy planning may not be available in resource-constrained set-up. Surface anatomy based planning has its own limitation in terms of adequately covering target due to variation of anatomy and tumor growth and spread pattern. Hence, improvisation of radiotherapy planning of cervical cancer, commonest malignancy among women in this set-up, utilizing locally available resource may improve treatment quality.Soldering lead wire, plumber's measuring tape, diagnostic x-ray and transpore adhesive tape were utilized to delineate radiotherapy portals for management of cervical cancer. Delineation of radiotherapy portals for irradiation of different regions in selected patients of carcinoma cervix is feasible in resource-constrained set-up. Radiotherapy delivery by conventional 2-D technique through the portal designed by utilizing soldering lead wire and diagnostic x-ray was achievable. Radiotherapy portal so delineated need to be validated in future clinical studies.